Sprachkontrastive Lokalisierung in Audioguides - Roncoroni, Tiziana (Scripta manent (Ljubljana), 2025)
This study conducts a contrastive linguistic analysis of strategies for the spatial orientation of audioguide users in building complexes. The empirical case study, examining four audioguides in the German–Italian language pair (two originals and two translations), focuses on macro- and micro-orientation, revealing clear tendencies. The two German audioguides more frequently exhibit deictic expressions and a higher information density concerning accumulations of localising elements and secondary lo-calisation. Conversely, the two Italian audioguides prefer more explicit, less dense localisations and dynamic verbs. Spatial logic (Raumlogik) and the intrinsic reference frame predominate across all four audioguides, with the absolute and relative reference frames also playing a significant role. Listeners more frequently function as the figure in the spatial schema in the two original audioguides. Orientation by means of imaginary wandering is primarily evidenced in the Italian original audioguide. Future research should, among other aspects, analyse language-specific means, and investigate actual listener reception.
Keywords: audio guides; Audioguides; avdiovodniki; dinamična lokalizacija; dynamic localisation; dynamische Lokalisierung; German–Italian language pair; jezikovni par nemščina–italijanščina; macro-synchronisation; makrosinronizacija; Makro-Synchronisation; micro-synchronisation; mikrosinhronizacija; Mikro-Synchronisation; Sprachenpaar Deutsch–Italienisch; static localisation; statična lokalizacija; statische Lokalisierung